2021
DOI: 10.1177/00405175211043251
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental approach towards an energy-efficient compact spinning system

Abstract: Compact spinning with a lattice apron has recently become a very attractive approach for pneumatic compact yarn production spinning systems. One of the main challenges with use of this method is the high negative pressure that leads to high energy consumption. In response to this challenge, we present a numerical and experimental investigation of the effects of a three-dimensional (3D) printed guiding device on the airflow characteristics and yarn properties. Initially, the 3D numerical model of the compact sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the use of negative pressure airflow to condense the fiber can elevate energy consumption during the spinning process. 7,70 In response to this challenge, Saty et al 129 developed a novel guiding mechanism for use in the condensing zone (Figure 24(a)). The numerical simulation outcomes indicated that incorporating a guiding device with low negative pressure can decrease negative pressure while sustaining exceptional spun yarn quality, resulting in reduced costs for pneumatic compact spinning.…”
Section: The Cost Economy Of the Compact Spinningmentioning
confidence: 99%
“…Furthermore, the use of negative pressure airflow to condense the fiber can elevate energy consumption during the spinning process. 7,70 In response to this challenge, Saty et al 129 developed a novel guiding mechanism for use in the condensing zone (Figure 24(a)). The numerical simulation outcomes indicated that incorporating a guiding device with low negative pressure can decrease negative pressure while sustaining exceptional spun yarn quality, resulting in reduced costs for pneumatic compact spinning.…”
Section: The Cost Economy Of the Compact Spinningmentioning
confidence: 99%
“…These guides were classified as the fully closed type, the upper opening type, and the two-side opening type. Saty et al 15,16 developed three different air guides for the lattice-apron compact spinning system. In their study, air guides with a downward-sloping slot on one side and two small holes at the top were the best.…”
mentioning
confidence: 99%